Emergence of wasp dope in rural Appalachian Kentucky. (13th November 2020) - Young, April M.; Livingston, Melvin; Vickers‐Smith, Rachel; Cooper, Hannah L. F.
Abstract: Background and aims: Recent reports have highlighted the emergence of 'wasp dope' as an issue of concern, but epidemiological evidence is lacking. Wasp dope is a crystalline substance created by electrifying pyrethroid‐containing insecticides (e.g. wasp sprays) that may give users a methamphetamine‐like 'rush'. This paper describes wasp dope use and correlates of use in a sample of people who use drugs (PWUD) in Appalachian Kentucky, a region that has been an epicenter of opioid use and related harms in the United States. Methods: Respondent‐driven sampling and targeted street outreach were used to recruit PWUD. Eligibility criteria included being aged at least 18 years, residing in one of five Appalachian Kentucky counties, and having either used opioids or injected any drug to get high in the prior 30 days. Interviewer‐administered surveys queried participants' ( n = 278) recent (past 6 months) wasp dope use, other substance use and demographic characteristics. Prevalence ratios (PR) were estimated using generalized estimating equations assuming a Poisson outcome distribution in a cross‐sectional analysis. Results: Recent wasp dope use was reported by 16.1% of participants. Men and people who recently experienced homelessness and transportation difficulties were twice or more as likely to have used wasp dope compared with their counterparts [PR = 2.08, 95% confidence interval (CI) = 1.11, 3.87, PR = 2.78, 95% CI = 1.64, 4.72 and PR = 2.01, 95% CI = 1.06–3.81, respectively]. While wasp dope use was associated with injection drug use and using opioids and other substances to get high in unadjusted analyses, the factor most strongly associated with wasp dope use was methamphetamine use (PR = 17.23, 95% CI = 2.57, 115.61), specifically methamphetamine injection (PR = 4.47, 95% CI = 1.56, 12.78). Conclusions: Among people who use drugs in rural Kentucky, USA, more than one in six people surveyed reported using wasp dope in the past 6 months, nearing the percentage using cocaine/crack (20%) and fentanyl/carfentanil (25%). Wasp dope use was higher among men and strongly associated with homelessness, transportation access, methamphetamine use and injection drug use.